Seasonal profile and level of CD4+ lymphocytes in the occurrence of cryptosporidiosis and cystoisosporidiosis in HIV/AIDS patients in the Triângulo Mineiro region, Brazil Perfil sazonal e nível de linfócitos CD4+ na ocorrência de criptosporidiose e cistoisosporidiose em pacientes HIV/AIDS na região do Triângulo Mineiro, Brasil - Márcia Benedita de Oliveira-Silva; Leonardo Rodrigues de Oliveira; Júlio César Possati Resende; Bethânea Crema Peghini; Luiz Eduardo Ramirez; Eliane Lages-Silva; Dalmo Correia (Revista da Sociedade Brasileira de Medicina Tropical, 2007)
Patients with AIDS are particularly susceptible to infection with intestinal coccidia. In this study the prevalence of infections with Cryptosporidium sp and Cystoisospora belli were evaluated among HIV/AIDS patients in the Triângulo Mineiro region, Brazil. Between July 1993 and June 2003 faecal samples from 359 patients were collected and stained by a modified Ziehl-Neelsen method, resulting in 19.7% of positivity for coccidian (8.6% with Cryptosporidium sp, 10.3% with Cystoisospora belli and 0.8% with both coccidian). Patients with diarrhoea and T CD4+ lymphocyte levels < 200 cells/mm3 presented higher frequency of these protozoans, demonstrating the opportunistic profile of these infections and its relationship with the immunological status of the individual. It was not possible to determine the influence of HAART, since only 8.5% of the patients positive for coccidian received this therapy regularly. Parasitism by Cryptosporidium sp was more frequent between December and February and thus was characterised by a seasonal pattern of infection, which was not observed with Cystoisospora belli. Pacientes com AIDS são particularmente susceptíveis a infecção por coccídios intestinais e nesse estudo foi avaliada a freqüência de Cryptosporidium sp. e Cystoisospora belli entre pacientes HIV/AIDS na região do Triângulo Mineiro, Brasil. No período de julho de 1993 a junho de 2003, amostras de fezes de 359 pacientes foram submetidas à coloração pelo método de Ziehl-Neelsen modificado, sendo detectada a presença de coccídios em 19,7% destas (8,6% de Cryptosporidium sp, 10,3% de Cystoisospora belli e 0,8% de ambos coccídios). Pacientes com diarréia e níveis de linfócitos T CD4+ < 200 células/mm3 apresentaram maior frequência destes protozoários, demonstrando o perfil oportunista destas infecções e a relação com o status imunológico do indivíduo. Não foi possível determinar a influência da HARRT, pois apenas 8,5% dos pacientes positivos para coccídios fazriam uso regular desta terapia. Parasitismo por Cryptosporidium ...